Analysis of deductive reasoning capabilities on circle materials in elementary mathematics learning - Siregar, Aviva Hanum; Wandini, Rora Rizky (Univeritas Papua, 2025)
Deductive reasoning ability is a reasoning skill that every student should possess in mathematics learning because it helps develop a systematic way of thinking in solving problems, particularly in the topic of circle circumference. However, in reality, many students still face difficulties in understanding this material. This study aims to identify students' abilities in performing calculations related to circle circumference and to assess their level of deductive reasoning. The research uses a qualitative descriptive approach with the subjects being sixth-grade students of MIN 7 Kota Medan, totaling 24 students who were then divided into three groups. The research subjects were selected using purposive sampling. The results show that students with a high level of deductive reasoning, coded as subject S1, achieved all indicators of deductive reasoning ability; students with a moderate level, coded as subject S2, met two indicators; and students with a low level, coded as subject S3, met only one indicator. The conclusion is that the higher a student's deductive reasoning ability, the more proficient they are in solving circle circumference problems.